Antioxidant and Antidiabetic Properties of Extracts from Three Underutilized Food Plants of North East India. Issue 2 (10th January 2023) - Goswami, Manab Jyoti; Dutta, Utpal; Seema, Tage; Bharali, Sourav Jyoti; Yanka, Hage; Tag, Hui; Bharali, Pankaj; Kakati, Dwipen
Abstract: Three underutilized leafy vegetables Sarcochlamys pulcherrima (Roxb.) Gaudich (SP), Ipomoea aquatica Forssk. (IA) and Zanthoxylum rhetsa (Roxb.) DC (ZR) were extracted with different solvents viz. 95 % ethyl alcohol, methanol and hot water. The extracts were evaluated for their antioxidant potential via DPPH, ABTS and FRAP assay along with electroanalytical studies using cyclic voltammetry. The antidiabetic potential was determined by recording their α‐amylase and α‐glucosidase inhibitory assay. The total phenolic content (TPC), total flavonoid content (TFC) and the liquid chromatography‐mass spectrometry (LC/MS) based phytochemical profiles of the extracts were also determined. All three extracts of SP exhibited significant antioxidant capacity. The antidiabetic potential of the IA and ZR extracts was found to be higher than or at par with that of standard acarbose. LC/MS studies reveal the presence of hitherto reported antioxidant and antidiabetic compounds like gamma‐aminobutyric acid, cinnamic acid, caffeic acid, α‐viniferin, piperlonguminine, niacin, kaempferol, etc., in the extracts. Abstract :